O ICMS como reflexo do desenvolvimento econômico dos municípios do Estado de Sergipe - Silva, Pedro da (2013)
Each month the Department of Finance makes the transfers of ICMS ( Tax on circulation of goods and transport services interstate and intercity communication ) to 75 municipalities of the state of Sergipe . These transfers contribute significantly to an increase in the share of revenues from municipal territories . As will be seen , the share of each municipal entity in GST revenue is expected in the Federal Constitution and follows one of the basic principles of income transfers is that the principle of derivation . Thus, the present study is to investigate the proposed GST as a reflection of economic development of the municipalities of the state of Sergipe . The first chapter presents a mapping on the historicity and economic particularities of the state tax ICMS. The second chapter shows the share of ICMS collection of Sergipe State in relation to other northeastern states and Brazil, but also analyzes the ICMS transfers to the municipalities of the State of Sergipe and ranking to determine which municipalities receive more GST than others, it is the method used Pearson correlation analysis to investigate the extent to which some explicit variables in the model are related or not performance of ICMS territorial units cited . The third chapter shows the income elasticity of the ICMS municipalities in Sergipe showing the extent to which GDP explains the analysis of these transfers . The fourth chapter shows the importance of the tax as a source of current revenues for social investments of the respective municipalities . Finally , concluding remarks are made , showing the relationship of the tax transfers to the respective municipalities in Sergipe . The results showed that there is a concentration of ICMS tax revenues of a few municipalities, which are the ones with better economic performance. Municipalities which are the value added tax justifies the largest transfer of state revenue.